O quinto momento do homem: ética e dignidade - Meira, Hérbat Spencer Batista (2006)
This work has as objective to rise stages of the human beings dignity evolution and its superposing with the entirety and the men s activities development, until its elevation as a constitutional principle and its evolution as a judicial decisions vector, being important to register that conviction ethics or convenience ethics imposes the existence of the constitutional principle. Human beings dignity principle deals about a historic and cultural, politic and social and economical construction, whose sloping is violently imposed to the production resources, which drives the present work through a trial of clarifying and aggregating all those nuances of the men s stages until they find out, welcome and construct the human beings dignity in all its subjective and objective aspects. The adopted research method was based in historic enrolment of the appearance among people since the bases of the word dignity until the acceptation of this value in the Brazilian society. This research searched dignity s doctrinaire valuation at the juridical point of view and the way of appreciation of this value, in its condition of constitutional principle, by the Brazilian Judicial Power. The work concludes that man and Law s evolution, in this moment, exposes, necessarily, an ethical posture in favor of dignity